Conference on Lasers and Electro-Optics 2012 2012
DOI: 10.1364/qels.2012.qtu2h.8
|View full text |Cite
|
Sign up to set email alerts
|

Pulse compression of phase-matched high harmonic pulses from a time-delay compensated monochromator

Abstract: Single 32.6 eV high harmonic pulses from a time-delay compensated monochromator were compressed down to 11 ± 3 fs by completely compensating for the pulse-front tilt. The photon flux was intensified up to 5.7×10 9 photons/s on target by implementing high harmonic generation under a phase matching condition in a hollow fiber used for increasing the interaction length. The output photon flux on target from the monochromator was comparable to that from a small synchrotron facility, while the pulse duration was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 7 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…Indeed, with monochromators based on a single-grating working in an off-plane geometry only XUV pulses with a time duration of few tens of fs have been reported so far [37,38]. Comparable results in terms of time duration can be obtained with a TDCM [39], which further allows for the generation of shorter pulses, of the order of 10 fs [40] or less [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, with monochromators based on a single-grating working in an off-plane geometry only XUV pulses with a time duration of few tens of fs have been reported so far [37,38]. Comparable results in terms of time duration can be obtained with a TDCM [39], which further allows for the generation of shorter pulses, of the order of 10 fs [40] or less [6].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, based on a cross-correlation picture, we will introduce a simple analytical expression that can be used to obtain a first rough estimation of the XUV pulse duration. Finally, we will compare the cross-correlation model [40,43] with the ePIE reconstruction, discussing the advantages of the latter.…”
Section: Simple Modelmentioning
confidence: 99%
“…However, we observed that the ring opens at around 500 fs upon excitation from the HOMO to the 3p x -Rydberg state via two-photon absorption (2PA) using 3.1 eV photons, which is much slower than that observed in case of 1PA. In this experiment, we employed time-resolved photoelectron spectroscopy (TR-PES) using an isolated single-order harmonic at 29.5 eV [28] that was selected using a time-delay compensated monochromator [41][42][43][44]. Thus, another motivation of the present study is to confirm the delayed ring-opening of CHD upon 2PA by a spectroscopic method other than TR-PES; therefore, in this study, we employed TR-HHS.…”
Section: Ultrafast Photo-isomerization Of 13-cyclohexadienementioning
confidence: 99%
“…The first grating is demanded to perform the spectral selection on an intermediate slit; the second grating compensates for the pulse-front tilt of the diffracted beam by equalizing the length of the optical paths, giving a temporal resolution much higher than the single-grating design. Double-grating instruments have been demonstrated to be very effective for HHs, with time resolution well below 10 fs [43][44][45][46][47]. The choice between the two options has to be performed as a trade-off between efficiency and throughput, which are maximized in the single-grating design, and temporal resolution, which is maximized in the doublegrating design.…”
Section: Introductionmentioning
confidence: 99%